Sustainable Fabrication of Green Chemistry Silica-Carbon Composites Derived from Coconut Coir and Dicalite Using Ion Exchange Method - Lely Amoi; Adinda Dwi Febriana; Srie Muljani; Suprihatin; Nurul Widji Triana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This research aimed to synthesise sustainable silica–carbon composites derived from coconut coir and dicalite diatomite using an ion-exchange-assisted sol–gel method and to evaluate the effects of gel-forming pH and carbonisation temperature on the resulting composite characteristics. The investigated parameters included gel formation pH 5 and carbonization temperature (400–800 °C). FTIR, XRD, and SEM–EDX analyses were applied to determine functional groups, phase structure, elemental composition, and surface morphology. The results revealed that the composite synthesised at pH 5 and carbonised at 800 °C exhibited the optimal structural properties. This condition produced a homogeneous morphology, balanced silica–carbon integration, reduced sodium residue, and a stable amorphous phase without crystalline formation. Higher carbonization temperatures enhanced siloxane network condensation and improved interfacial bonding between silica and carbon phases. The synthesis guidelines for silica-carbon composite fabrication should therefore emphasise controlled acidic gel formation and high-temperature carbonisation to produce structurally stable, well-integrated materials suitable for adsorption and environmental applications. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 9: Industry, Innovation and Infrastructure